Kesejahteraan Keluarga pada Ibu yang Bekerja sebagai Perawat - arni nur rahmawati (Universitas Harapan Bangsa Purwokerto, 2019)
The times and increasingly modern technology, encourage a mother to work for financial reasons, self-actualization, and relationships. This makes women workers especially mothers work as vulnerable groups and at risk of occupational health hazards. One of them is the role imbalance between work and family due to multiple roles. This can make the mother work stressful so that it will affect the well-being condition of the mother working in the family. The purpose of this study was to describe the family well-being of mothers who worked as nurses. The design used in this study was descriptive quantitative with 52 respondents who were the results of screening based on inclusion criteria. Family well-being data were analyzed using descriptive analysis. The results of this study indicate the average value of family well-being in mothers who work as nurses is 123.33. The family well-being component consists of the unity of the family system including the relationship of family structure; the relevance of functions or roles in carrying out tasks in the family; and prevent family vulnerability to other influences such as genetic, physiological, sociological or psychological. Based on these results, it can be concluded that family well-being can describe the ability of the mother to work in adapting to her dual role.